Riekophlebia crocina, a new genus and species of Atalophlebiinae (Ephemeroptera: Leptophlebiidae) from the Wet Tropics bioregion of north-eastern Australia - Christidis, Faye (Zootaxa, 2009)
Riekophlebia crocina, a new genus and species, is described from Australia based on nymphs and adults. Riekophlebia belongs to a lineage that also includes the Australian genera Austrophlebioides, Kirrara, Manggabora and Tillyardophlebia.